Influence of individual, work-related and organizational factors on adherence to standard precautions by dental professionals - Vicente Goncalves, Patrick Raphael [UNESP]; Martins, Ronald Jefferson [UNESP]; Saliba Moimaz, Suzely Adas [UNESP]; Marcal Mazza Sundefeld, Maria Lucia [UNESP]; Isper Garbin, Artenio Jose [UNESP]; Saliba Garbin, Clea Adas [UNESP] (Univ Santa Cruz Do Sul, 2016)
Background and Objectives: Individual, work-related and organizational factors may favor adherence to safety practices in the work environment, preventing exposure to biological material among health professionals. Based on that, the aim of the study was to verify the influence of individual, work-related and organizational factors on adherence to standard precautions. Methods: This is a cross-sectional study with a census survey design and a quantitative approach, carried out with 79 dental professionals (dentists and oral health assistants), allocated in the public health system of a municipality in Sao Paulo. For data collection, the participants answered the explanatory model of adherence to standard precautions. This is a validated questionnaire consisting of demographic and psychometric scales, where the association between these factors and adherence to standard precautions was obtained by multiple logistic regression analysis. Results: Statistical analysis showed that the professional's age, work experience in the profession and time working at the unit; how the professional learned about standard precautions, the risk personality, the prevention effectiveness, the difficulties to follow standard precautions, training and availability of personal protective equipment; the management's support to worker safety, safety performance feedback and knowledge of occupational transmission of HIV, in addition to the workload, positively influenced adherence to standard precautions among professional participating in the study. Conclusion: We conclude that adherence to standard precautions is simultaneously influenced by individual, work-related and organizational factors.
Keywords: Knowledge; Universal Precautions; Safety Management; Occupational Health; Exposure to Biological Agents